1708b The immunotoxicity and neurotoxicity of aluminium. (24th April 2018) - Niu, Q; Zhang, Q; Li, H; Wang, L; Lu, X
Abstract : Aluminium is omnipresent in the world, accounts 8.6% of the crust, and believed to be a neurotoxicant for a lot of years, and thought to be related with Alzheimer's disease and other neurodegenerative disease. In recent decades, aluminium, as metals, chemical compounds, powders, additives, adjuvants, and nanoparticles have being utilised widely in many fields including human's daily life and industries, and their potential adverse effect on health drew great concern. Aluminium, in the forms of ions, chemical compounds, fine particulate matters, can be ingested, inhaled, or even injected into human body, and translocated into blood stream and immune system to induce immutoxicity, and into central nervous system to induced neurotoxicity. Aluminium may induce neumocytes apoptosis by triggering oxidative stress, and inhibit or activate activity of cytokins, and the immuotoxicity and neurotoxicity induced by aluminium ions and fine aluminium particulate matters was higher than that of relatively large aluminium particles. Besides though blood compartment by which aluminium damage the blood brain barrier, it may enter into central nervous system though olfactory nerve. Aluminium impair behavioural performance of model organisms and rodents. The mechanisms of Al-induced immune and neurotoxicity may be: aluminium induces neural cell death by triggering oxidative stress, apoptosis, necroptosis and autophagy through complicate cell signal transmission pathways; promote Aβ deposit, promote tau hyperphosphorylation, and together induce neurodegeneration. promote cytokine release, trigger inflammation and immune reactions, and damage DNA and induce epigenetic changes.